Design and characterization of a new three-stage quadruple pass EDFA - Akhter, Fowzia; Ibrahimy, Muhammad Ibn; Naji, Ahmed Wathik; Siddiquei, Hasin Reza (Asian Network for Scientific Information, 2012)
Low loss long haul Optical Fiber Communication System (OFCS) is the key challenge in today’s research. Multi-stage Erbium-Doped Fiber Amplifier (EDFA) provides high gain, low noise figure and long distance transmission. Development of multi-stage EDFAs has become one of main research areas in recent times. In this study, a three-stage Quadruple Pass (QP) EDFA is proposed for long haul OFCS. The mathematical models to characterize this proposed EDFA are developed. In the mathematical models, the effects of Amplified Spontaneous Emission (ASE) of prior stages are included. Performance analysis of this QP EDFA is carried out with the variation of input pump power ratio and signal power. A maximum gain of 59.94 dB is achieved corresponding -33 dm input signal power at 1550 nm wavelength. Change in erbium ions concentration in energy level 1 (N1) and energy level 2 (N2) with the variation of fiber length is also analyzed to determine optimum fiber length. From the obtained results the optimum design parameters (pump power, signal power, fiber length) are recommended for practical implementation.